Epidemiology of elite sprint kayak injuries: A 3-year prospective study. Issue 10 (October 2019) - Toohey, Liam A.; Drew, Michael K.; Bullock, Nicola; Caling, Britt; Fortington, Lauren V.; Finch, Caroline F.; Cook, Jill L.
Abstract: Objectives: To analyse the characteristics of injuries sustained by elite sprint kayak athletes, to investigate relationships between initial and subsequent injuries, and to examine injury differences between male and female athletes. Design: Descriptive epidemiology study. Methods: Data from 63 athletes (37 male, 26 female) of the Australian national sprint kayak squad were prospectively collected over three continuous years (September 2014-August 2017). All medical attention injuries were recorded irrespective of time-loss and modality of training. Descriptive analyses were performed, and frequency comparisons across genders assessed with chi squared tests. Results: Forty-nine athletes (78%) sustained 146 injuries (median = 2, interquartile range = 1–4, range = 0–12). Most injuries were to the upper limb (48%), with the shoulder being the most common body site injured (27%). Thirty-one athletes (49%) sustained at least one subsequent injury, equating to 97 subsequent injuries. The majority (68%) of subsequent injuries occurred at a different site and nature to previous injuries. Male athletes were more likely to sustain an injury than remain injury free compared to female athletes (Chi 2 (1) = 6.75, p = 0.009), but there was no difference between males and females who thereafter sustained a subsequent injury (Chi 2 (1) = 0.84, p = 0.359). Conclusions: Injury occurrence is common in sprint kayak, with many athletes experiencing more than one injury. Small variations in injury characteristics exist between male and female athletes in sprint kayak. This study identifies upper limb and trunk, and joint and muscle injuries as the most prevalent sprint kayak injuries, providing a focus for the development of future injury prevention strategies.